Body mass index is a barrier to obesity treatment - Chin, Geoffrey C.; Potter, Adam W.; Friedl, Karl E. (Frontiers in Endocrinology, 2024)
The Food and Drug Administration's (FDA) obesity drug guidance is set on the basis of body mass index (BMI), with thresholds of either BMI ≥30 or BMI ≥27 kg/m 2 with weight-related comorbidities. While BMI is associated with obesity-related health outcomes, there are known limitations to use as a direct measure of body fat or metabolic health, and the American Medical Association has highlighted limitations of BMI in assessing individual obesity risks. BMI thresholds impose a barrier to treatment. In a sample from the NHANES dataset (n=6,646 men and women), 36% of individuals with metabolic syndrome (MetS) may not be eligible for obesity pharmacotherapy. This analysis provides quantifiable justification for refinement of the BMI treatment criteria with a more holistic assessment of individual obesity-related disease risk.